Stroke and the Orthopaedic Surgeon - Banskota, AK (Nepal Orthopaedic Association Journal, 2013)
The role that can be effectively played by the orthopaedic surgeon in the long-term management of the stroke victim is often overlooked. Post-stroke patients rely heavily on the orthopaedist, amongst other members of the multidisciplinary team, to regain the maximum possible functional status following the stroke event. A great need to understand and implement the principles of post-stroke orthopaedic treatment and rehabilitation exists in our own community and practice. DOI: http://dx.doi.org/10.3126/noaj.v2i1.8139 Nepal Orthopaedic Association Journal Vol.2(1) 2011: 43-46